Chemotherapy at First Diagnosis of Advanced Prostate Cancer – Revolution or Evolution? Findings from a British Uro-oncology Group UK Survey to Evaluate Oncologists' Views on First-line Docetaxel in Combination with Androgen Deprivation Therapy in Castrate-sensitive Metastatic and High-risk/Locally Advanced Prostate Cancer. Issue 6 (June 2016) - Davda, R.; Hughes, S.; Jones, R.; Crabb, S.J.; Troup, J.; Payne, H.
Abstract: Aims: There have been three randomised trials investigating docetaxel in combination with androgen deprivation therapy as first-line therapy for hormone-sensitive metastatic and locally advanced/high-risk prostate cancer. The largest of these studies, UK STAMPEDE trial, recently presented in June 2015. The aim of this survey was to evaluate if oncologists' practice has changed as a result of these studies, or if their practice is likely to change in different clinical settings in the future. Materials and methods: The British Uro-oncology Group issued a semi-structured online questionnaire to its membership of 160 specialist urological oncologists practising in the UK. Links to the abstracts of GETUG-AFU-15, E3805 CHAARTED and STAMPEDE were attached with the survey for respondents to review before completing the survey. Results: In total, 111 participants completed the survey; 87% stated that STAMPEDE will influence their clinical practice in the future. Almost all (96%) would offer docetaxel with androgen deprivation therapy to men presenting with high volume metastatic prostate cancer. Fewer oncologists would offer this treatment to men with low volume metastatic prostate cancer, locally advanced or relapsed disease. Various patient- and disease-related factors were considered in decision making, as well as resource implications. Conclusions: This survey reports oncologists' attitudes towards a major change in practice in the standard of care for men with newly diagnosed advanced prostate cancer in the UK. The survey highlighted the complexities surrounding the clinical implementation of the data from these studies, including changes in referral pathways, with the early involvement of oncologists in such patients' care, increases in workloads for oncologists and chemotherapy units and the need for national approval for re-imbursement of these treatments. Highlights: In high volume metastatic disease, 96% of uro-oncologists would offer early docetaxel. Patient selection for early chemotherapy in castrate sensitive disease is complex. Changes in practice will have implications on treatment pathways and resources.